DESIGN AND IMPLEMENTATION OF STUDENT LEADERSHIP DEVELOPMENT AT SMAIT NFBS BOGOR - Purwoko, Lukman Fajar; Juwita, Rahmi; Hariyati, Nunuk (Journal of Learning on History and Social Sciences, 2025)
Objective: The study of student leadership development programmes is an important variable in building a great and advanced nation. However, not many schools in Indonesia have studied this. Some studies show that student leadership programmes have a positive impact. SMAIT NFBS Bogor is a school established with the main purpose of training future Islamic leaders. This study is important to provide a basic description of student leadership development at SMAIT NFBS Bogor, so that it becomes one of the references for the development of future Islamic leaders. Method: The method used is a qualitative method, which involves conducting interviews with various stakeholders such as the person in charge of the programme, the school committee, and student representatives. Results: The basic framework of student leadership development is through mentoring, extracurricular activities, learning and acculturation. The implementation of student leadership development will result in the development of students' and parents' understanding of the leadership programmes developed by the school, and the development of students' leadership skills and abilities. Novelty: The leadership training at NFBS Bogor from the coaching aspect includes Leadership School Level I, II, III and IV, Leadership Forum and Coaching. The empowerment aspect is being involved as a committee, student management in the association, extracurricular, class and student council.